Pengaruh Suhu pada Ekspresi Pretrombin-2 Manusia Rekombinan di Escherichia coli ER2566 - Silaban, Saronom; Simorangkir, Murniaty; Maksum, Iman Permana; Hasan, Khomaini (Universitas Negeri Medan, 2018)
Human recombinant prethrombin-2 (rhPT-2) was expressed in Escherichia coli. Previous studies reported that the expression of rhPT-2 in E. coli tends to formed inclusion body. This study aims to determine the effect of temperature on the expression of rhPT-2 in E. coli ER2566. This study begins with the isolation of recombinant plasmids, competent cell preparation and transformation of competent cells of E. coli ER2566 strain, and rhPT-2 gene expression with various induction temperatures 12, 18, 22 and 30°C. Characterization results showed that the induction temperature of 22°C was the optimum temperature of rhPT-2 gene expression as a soluble fraction in E. coli ER2566 with IPTG concentration 0.1 mM. These results prove that the temperature affects the expression of rhPT-2 in E. coli ER2566. [EFFECT OF TEMPERATURE ON RECOMBINANT HUMAN PRETROMBIN-2 EXPRESSION IN ESCHERICHIA COLI ER2566] (J. Sains Indon., 42(2): 25-30, 2018)Keywords:Induction Temperature, Soluble Fraction, Prethrombin-2, E. coli ER2566